Myeloid-Derived Suppressor Cells in Tumors: From Mechanisms to Antigen Specificity and Microenvironmental Regulation - Yang, Yuhui; Li, Chunyan; Liu, Tao; Dai, Xiaofang; Bazhin, Alexandr V. (Frontiers in Immunology, 2020)
Among the various immunological and non-immunological tumor-promoting activities of myeloid-derived suppressor cells (MDSCs), their immunosuppressive capacity remains a key hallmark. Effort in the past decade has provided us with a clearer view of the suppressive nature of MDSCs. More suppressive pathways have been identified, and their recognized targets have been expanded from T cells and natural killer (NK) cells to other immune cells. These novel mechanisms and targets afford MDSCs versatility in suppressing both innate and adaptive immunity. On the other hand, a better understanding of the regulation of their development and function has been unveiled. This intricate regulatory network, consisting of tumor cells, stromal cells, soluble mediators, and hostile physical conditions, reveals bi-directional crosstalk between MDSCs and the tumor microenvironment. In this article, we will review available information on how MDSCs exert their immunosuppressive function and how they are regulated in the tumor milieu. As MDSCs are a well-established obstacle to anti-tumor immunity, new insights in the potential synergistic combination of MDSC-targeted therapy and immunotherapy will be discussed.